Organization Structure and Corporate Social Performance: A Field Study in Two Contrasting Industries - Bhambri, Arvind; Sonnenfeld, Jeffrey (Academy of Management Journal, 1988)
The relationship between public-affairs management structure and social performance was studied. We explored three dimensions of public-affairs management structure?receptivity to public affairs information, integration of public affairs information, and internal influence of public affairs?in two contrasting industries, insurance and forest products. Balanced strength along each of the three dimensions of public affairs management was found to be associated with high social performance in both industries. The pattern was more consistent for companies at the extremes of social performance ratings than it was for middle-ranked companies. In addition, differences in the institutional environments of the two industries were associated with differences in the various components of public affairs structure.